The fragile threads of power [large type] - Schwab, Victoria (Schwab, Victoria. Threads of power, 2023)
"Once, there were four world, each connected by a single city: London. Until magic forced the worlds to seal the doors between them. The magicians who could still open the doors grew rare, and now only three Antari are known in recent memory--Kell Maresh, Delilah Bard, and Holland Vosijk. But a new Antari has appeared. Amidst this tapestry of old friends and new enemies, a girl with unusual magic ability comes into possession of a device that could change the fate of all four worlds. Her names is Tes, and she's the only one who can bring them together--or unravel it all"--